Empowering Cadres In Preparing The Community To Face The New Normal Era In Jabungan Banyumanik Village, Semarang City - Eliyah, Eliyah; Wijayanta, Setya; Putri, Niken Aulia (Jurnal Health Sains, 2024)
Special attention to health issues is still the main focus of the government in Indonesia. Some health aspects that are of concern include health degrees, cross-sectoral cooperation, health development policies, health development financing systems, quality of health facilities, health workers, and health supplies (Suparyanto, 2010). These health problems can affect the general public as well as certain groups such as infants, toddlers, pregnant women, the elderly, and workers. The purpose of this study is to run the Tri Darma of higher education by implementing community service activities, especially in the form of preparing health cadres to face the New Normal Era in Jabungan Banyumanik Village, Semarang City. The implementation method includes a preparatory stage that involves coordinating with health cadres, identifying participants, compiling materials, and carrying out activities using lectures, demonstrations, and discussion methods. Evaluation is carried out through pretest and posttest to measure the increase in cadre knowledge. Findings from the study showed that there was an increase in cadre knowledge by 15%. The impact of this research is improving the quality of health cadres, public understanding of the New Normal Era, and strengthening cooperation between universities and the community. Therefore, increasing the knowledge and skills of cadres, as well as community understanding, is expected to have a positive impact on health services and preparation for new situations.